Explore BrainMass

Explore BrainMass

    Solving functions

    Not what you're looking for? Search our solutions OR ask your own Custom question.

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    Given f(x)= 4x squared - 3x + 2 and g(x)= 3x - 2, find each of the following. simplify the expression if possible.

    a. f(-5)

    b. f(x+h) - f(x)/ h

    c. (f o g)(x)

    © BrainMass Inc. brainmass.com December 24, 2021, 4:50 pm ad1c9bdddf
    https://brainmass.com/math/algebra/simplified-functions-expressed-11043

    SOLUTION This solution is FREE courtesy of BrainMass!

    a) f(-5) = 4 * (-5)^2 - 3*(-5) + 2 ( replacing x by -5)
    = 100 + 15 +2
    = 117.

    b) f(x+h)-f(x)/h = (4(x+h)^2 - 3*(x+h)+2 - (4x^2 - 3x +2))/h
    = (4x^2 + 4h^2 +8xh - 3x -3h + 2 - 4x^2 +3x-2)/h
    = (4h^2 + 8xh -3h)/h
    = 4h +8x - 3

    c) (fog)(x) = f(g(x))
    = f( 3x-2)
    = 4 (3x-2)^2 -3(3x-2)+2
    = 4( 9x^2-12x+4)-9x+6+2
    = 36x^2-48x+16-9x+8
    = 36x^2-57x+24
    Hope it is clear.

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    © BrainMass Inc. brainmass.com December 24, 2021, 4:50 pm ad1c9bdddf>
    https://brainmass.com/math/algebra/simplified-functions-expressed-11043

    ADVERTISEMENT